The safety and pharmacokinetics of metformin in patients with chronic liver disease. Issue 5 (21st January 2020) - Smith, Felicity C.; Stocker, Sophie L.; Danta, Mark; Carland, Jane E.; Kumar, Shaun S.; Liu, Zhixin; Greenfield, Jerry R.; Braithwaite, Hannah E.; Cheng, Tim S.; Graham, Garry G.; Williams, Kenneth M.; Day, Richard O.
Summary: Background: The FDA approved 'label' for metformin lists hepatic insufficiency as a risk for lactic acidosis. Little evidence supports this warning. Aims: To investigate the safety and pharmacokinetics of metformin in patients with chronic liver disease (CLD). Methods: Chronic liver disease patients with and without type 2 diabetes mellitus (T2DM) were studied by a cross‐sectional survey of patients already prescribed metformin (n = 34), and by a prospective study where metformin (500 mg, immediate release, twice daily) for up to 6 weeks was prescribed (n = 24). Plasma metformin and lactate concentrations were monitored. Individual pharmacokinetics were obtained and compared to previously published values from healthy and T2DM populations without CLD. Results: All plasma metformin and lactate concentrations remained below the putative safety thresholds (metformin, 5 mg/L; lactate, 5 mmol/L). Lactate concentrations were unrelated to average steady‐state metformin concentrations. In patients with CLD, T2DM was associated with higher plasma lactate concentrations (48% higher than those without T2DM, P < 0.0001). CLD patients with cirrhosis had 23% higher lactate concentrations than those without cirrhosis ( P = 0.01). The pharmacokinetics of metformin in CLD patients were similar to patients with T2DM and no liver disease. The ratio of apparent metformin clearance (CLMet /F) to creatinine clearance was marginally lower in CLD patients compared to healthy subjects (median, interquartile range; 12.6, 9.5‐15.9 vs 14.9, 13.4‐16.4; P = 0.03). Conclusions: The pharmacokinetics of metformin are not altered sufficiently in CLD patients to raise concerns regarding unsafe concentrations of metformin. There were no unsafe plasma lactate concentrations observed in CLD patients receiving metformin (ACTRN12619001292167; ACTRN12619001348145).